AMPA Receptor Function in Hypothalamic Synapses - Royo, Maria; Escolano, Beatriz Aznar; Madrigal, M. Pilar; Jurado, Sandra (Frontiers in Synaptic Neuroscience, 2022)
AMPA receptors (AMPARs) are critical for mediating glutamatergic synaptic transmission and plasticity, thus playing a major role in the molecular machinery underlying cellular substrates of memory and learning. Their expression pattern, transport and regulatory mechanisms have been extensively studied in the hippocampus, but their functional properties in other brain regions remain poorly understood. Interestingly, electrophysiological and molecular evidence has confirmed a prominent role of AMPARs in the regulation of hypothalamic function. This review summarizes the existing evidence on AMPAR-mediated transmission in the hypothalamus, where they are believed to orchestrate the role of glutamatergic transmission in autonomous, neuroendocrine function, body homeostasis, and social behavior.